CAROs: Climate risk-adjusted refinancing operations - Florian Böser; Chiara Colesanti Senni (ETH Zurich, CER-ETH - Center of Economic Research, 2021)
Policy makers have argued that markets are not pricing climate risk appropriately yet, which may lead to a misallocation of resources and financial instability. Climate riskadjusted refinancing operations (CAROs) conducted by the central bank are one possible instrument to address this issue. CAROs are characterized by interest rates on reserve loans, which depend on the climate risk exposure of the assets held by the borrowing bank. If private agents and the central bank have differing beliefs about the likelihood of the transition to a low-carbon economy, the allocation emerging without CAROs is, from the central bank's perspective, suboptimal and may lead to financial instability. We find that an appropriate design of CAROs allows the central bank to influence bank lending in a way that induces the optimal allocation under its beliefs and eliminates financial instability. Moreover, we show that investment into climate risk mitigation reduces the need for central bank intervention, and that CAROs can be used to achieve specific climate-related allocation targets.
Keywords: D84; E42; E43; E44; E58; G21; Q50; 330; central bank; banks; refinancing operations; interest rates; climate risk